Prediksi Kebutuhan Energi Listrik Menggunakan Metode Jaringan Syaraf Tiruan - Pulungan, Joliando; Novita, Rice (Building of Informatics, Technology and Science (BITS), 2022)
Government owned company of electricity play an important role in the distribution of electrical energy services. The Bagan Batu Auxiliary Service Unit (ULP) is one of the ULPs that plays an important role in the distribution of electrical energy in the Bagan Batu area. Along with the increase in the number of customers every year, the problem of demand for electrical energy changes and increases every year. To predict short-term electrical energy needs, this study uses the Backpropagation Artificial Neural Network method with the help of the MATLAB R2015B tool. The research data for training and network testing uses the history of energy sold (kWh) for the last 10 years with other variables consisting of household customers, business, social, industrial, population growth, Gross Regional Domestic Product (GRDP). The results of the research produce predictions of electrical energy for the next 3 years from 2022 to 2024. This research produces the best architectural model 6-6-1 with the smallest MSE error of 0.003312731 and produces Mean Absolute Percentage Error (MAPE) value of 6%. The research implies benefits for stakeholders to take action on the provision of electrical energy